From Symmetric Rifting to Asymmetric Spreading—Insights Into Back‐Arc Formation in the Central Mariana Trough - H.‐S. Hilbert; A. Dannowski; I. Grevemeyer; C. Berndt; S. Kodaira; G. Fujie; N. Takahashi (Geochemistry, Geophysics, Geosystems)
Abstract The Mariana Trough is the youngest back‐arc basin in a series of basins and arcs that developed behind the Mariana subduction zone in the western Pacific. Active seafloor spreading is ongoing at a spreading axis close to the Mariana Arc, resulting in a pronounced asymmetric configuration (double rate to the west 2:1) at 17°N. The formation of back‐arc basins is controlled by the subducting slab, which regulates the temporal development of mantle flow, entrainment of fluids, and hydrous melts together with the magma generation. To better understand the formation process of back‐arc basin asymmetry in the central Mariana Trough, we combined 2‐D P‐wave traveltime tomography results with high‐resolution bathymetric data. Here, we show that the crust in the central Mariana Trough is 6.5–9.5 km thick, which is unusually thick for oceanic crust. While the lower crust exhibits average seismic velocities of 6.5–7.2 km/s, high‐velocity anomalies occur at the margins of the Mariana Trough, indicating that magmatic accretion was affected by hydrous melting during rifting. While the Mariana Trough developed from a rather symmetric rifting (0.89:1) to a strongly asymmetric seafloor spreading stage (5.33:1), the contribution of hydrous melts declined and the opening direction changed at ∼5 Ma. Asymmetric basin opening is potentially driven by the far‐field stress effect of the subduction zones on the western boundary of the Philippine Sea Plate.